Dampak Game Online Pubg Terhadap Motivasi Belajar Remaja Di Desa Bakan Maja - Mohamad Hadi Pratama; Enjang Suherman (CV. ITTC INDONESIA, 2024)
This research aims to examine the impact of the online game PUBG on the learning motivation of teenagers in Bakan Maja Village. The PUBG game has become a popular phenomenon among teenagers, but its existence also influences their learning motivation, both positively and negatively. This study used a qualitative approach with a constructivist paradigm, involving in-depth interviews and observations to collect data from 15 teenagers who were addicted to playing PUBG. The research results show that the intensity of playing the PUBG game has a negative impact on teenagers' learning motivation, as seen from a decrease in academic grades, changes in social behavior and health problems. However, some teenagers also show increased motivation to learn through the social interactions that occur while playing games. In conclusion, there needs to be supervision and restrictions from parents to reduce the negative impact of addiction to the PUBG game. This research provides in-depth insight into the phenomenon of online game addiction and its implications for adolescent learning motivation, as well as offering recommendations for increasing learning motivation among adolescents.